OPTIMALISASI WORK-LIFE BALANCE DI TEMPAT KERJA MELALUI PSIKOEDUKASI DAN INTERVENSI - Nur, Zulfaidah; Firsada, M. Iqbal; Hidayat, Taufik; Komalasari, Shanty (Universitas Mataram, 2025)
The Standardization and Industrial Service Center (BSPJI) in Banjarbaru is facing the challenge of a high workload that affects the work-life balance of its employees, despite a supportive family-like work atmosphere. To address this issue, this community service activity aims to reduce burnout and stress while enhancing understanding of work-life balance (WLB) through psychoeducation and interventions such as the butterfly hug and ice breaking. The method involved 62 participants from ASN and PPNPN at BSPJI Banjarbaru, with a 90-minute session that included ice breaking to create a relaxed atmosphere, psychoeducation to provide knowledge about WLB, and the butterfly hug as a self-healing relaxation technique. Evaluation results showed that 95% of participants felt that the stress management techniques taught helped them manage work pressure better, and 100% understood the importance of balancing work and personal life. Additionally, 98% of participants reported a more positive work atmosphere after the activity, while 93% found the butterfly hug effective in relieving workplace stress. This activity also successfully increased motivation, self-confidence, and practical skills that can be applied in daily life, thereby improving the quality of life for employees. Thus, the psychoeducation training and interventions of butterfly hug and ice breaking effectively reduced burnout and stress among BSPJI Banjarbaru employees while promoting understanding and commitment to the importance of work-life balance in the workplace.